Mapping Game-Based Learning Research in Physical Education: A Bibliometric Analysis of Indonesian Scholarly Contributions (2014–2024) - Mas'odi Mas'odi; Ribut Wahyu Eriyanti; Joko Widodo; Nurul Zuriah (STAI Hubbulwathan Duri, 2026)
Through a bibliometric analysis, this study examines the development, patterns, and key trends in implementing game-based learning (GBL) within physical education. Despite the growing interest in GBL across various educational domains, its application in physical education remains underexplored and fragmented. To address this gap, a bibliometric analysis was conducted on 29 peer-reviewed journal articles indexed in Scopus and published between 2014 and 2024. The articles were systematically selected from an initial pool of 330 records using predefined inclusion and exclusion criteria. Data were analyzed using VOSviewer and CiteSpace to examine co-authorship networks, keyword co-occurrence, citation patterns, and publication trends. The results indicate a consistent increase in GBL-related research in physical education over the past decade, with notable contributions from Indonesian scholars. Key clusters include character development, digital media integration, cooperative learning, and motor skill enhancement. Highly cited articles emphasize the relevance of combining digital platforms such as YouTube and gamified instructional strategies to improve students' engagement and fundamental movement skills. However, challenges persist, particularly in technological access and educators' digital competencies. This study contributes to the literature by offering a comprehensive map of the research landscape and highlighting emerging gaps and opportunities for future inquiry. The findings imply that when effectively designed and supported, GBL can enhance physical, cognitive, and social-emotional outcomes in physical education. These insights are relevant for curriculum developers, policymakers, and educators seeking to modernize physical education through innovative, inclusive, and engaging pedagogical approaches in the digital era.